The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/bto.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Science in Orthopedic Oncology

Abstract: Limb salvage is widely practiced as standard of care in most cases of extremity bone sarcoma. Allograft and endoprosthesis reconstructions are the most widely utilized modalities for the reconstruction of large segment defects, however complication rates remain high. Aseptic loosening and infection remain the most common modes of failure. Implant integration, soft-tissue function, and infection prevention are crucial for implant longevity and function. Macro and micro alterations in implant design are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…All implants were manufactured by Zimmer Biomet, Stryker, DePuy Synthes, or Howmedica. Although there were changes in implant design, manufacturer, and metallurgy over the study period, surgical technique remained consistent regarding principles of tumor resection, canal preparation, implant cementation, and soft tissue closure as described in our group’s prior publications [4, 5, 10, 22, 33].…”
Section: Methodsmentioning
confidence: 99%
“…All implants were manufactured by Zimmer Biomet, Stryker, DePuy Synthes, or Howmedica. Although there were changes in implant design, manufacturer, and metallurgy over the study period, surgical technique remained consistent regarding principles of tumor resection, canal preparation, implant cementation, and soft tissue closure as described in our group’s prior publications [4, 5, 10, 22, 33].…”
Section: Methodsmentioning
confidence: 99%
“…Proximal femur replacements (PFRs) for oncologic indications have become a standard reconstructive approach after bone tumor excisions in that anatomic location. In recent decades, numerous studies from many centers have shown that proximal femur tumors can be treated with resection and reconstruction rather than ablative surgery [2-4, 10-12, 17].…”
Section: Where Are We Now?mentioning
confidence: 99%
“…A number of treatment methods have been designed so far in order to treat this tumor, these treatment methods are; chemical, thermal, mechanical, biotic, injection etc. These treatment methods were suggested to control this dreadful disease with the help of eradicating the tumor through curettage process [59]. The giant cells play a main role in the expression of calcitonin receptors which has been reported recently, giant cells mainly consist of osteoclasts in chronic giant cell granulomas (CGCGs).…”
Section: Giant Cell Tumor Of Bone (Gctb)mentioning
confidence: 99%